2022
DOI: 10.28945/4980
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Sustainable Adoption of E-Learning Systems: The Role of Self-Directed Learning

Abstract: Aim/Purpose: This study seeks to investigate the factors that influence online students’ continued usage intention toward e-learning systems by presenting an extended model that is based on the Delone and McLean (2003) IS success model (D&M ISS model). Background: The use of e-learning systems in this era has become a vital element of delivering higher education. Learning via e-learning systems has significant benefits that support conventional learning. Thus, it is crucial to measure the success of e-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 0 publications
4
66
0
Order By: Relevance
“…In their UTAUT meta-analysis, Dwivedi et al (2011) indicated a significant association between BI and AU behavior for eight studies considered in their article (Dwivedi et al , 2011). Many published academic studies, for example (Al-Adwan et al , 2022; Alkhwaldi and Abdulmuhsin, 2021; Lallmahomed et al , 2017; Lian, 2015), have only examined users’ intentions toward adopting IT/IS as an outcome construct.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their UTAUT meta-analysis, Dwivedi et al (2011) indicated a significant association between BI and AU behavior for eight studies considered in their article (Dwivedi et al , 2011). Many published academic studies, for example (Al-Adwan et al , 2022; Alkhwaldi and Abdulmuhsin, 2021; Lallmahomed et al , 2017; Lian, 2015), have only examined users’ intentions toward adopting IT/IS as an outcome construct.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, businesses and organisations that seek to extract emotions from their social media channels must scrutinise each API before selecting the best tool. This points to the significance of such studies that aim to help decision-makers by providing the necessary evaluation strategies [ [45] , [46] , [47] ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of effective e-learning as a means of online learning information systems at universities also depends on the level of student needs in using technology [5]. The quality of service and the availability of technology as a means of information system infrastructure can support sustainability education [6], [7].…”
Section: Introductionmentioning
confidence: 99%